Penghapusan ShÅ«shinkoyÅ (çµ‚èº«é›‡ç”¨) Menjadi Fenomena Muenshakai (ç„¡ç¸ç¤¾ä¼š) - Prabowo, Roberto Masami (Lingua Cultura, 2013)
Muenshakai is a phenomenon in Japanese society that relationship disappears and a growing number of people who live their own lives. This phenomenon occurs because of the abolition of the shÅ«shinkoyÅ (çµ‚èº«é›‡ç”¨) working system in about 1990. Declining in marriage rates, divorce, and declining in birth rates (å°‘ååŒ–) also lead to the formation of muenshakai. The problem limited to Japanese people around the year of 2007â€“2013, when the elderly Japanese people began to retire, lived alone, no relatives who could or would take care of them or even just going to visit. When they were sick, even died in the residence or in a public place, none of their family wanted to pay for hospital, funeral ceremony, and burial. To discuss this study, the author used descriptive analytical method. This research results the analysis of an image of contemporary Japanese society with economic issues that affect the family. The conclusion of the study states Japan must create a working system to ensure the communityâ€™s economy in the future.